COMPARISON OF BUPIVACAINE ALONE AND BUPIVACAINE PLUS LIDOCAINE IN SUPRACLAVICULAR BLOCK UNDER ULTRASOUND GUIDANCE - SAEED, R; RABIA, H; BUKHARI, S; KAKEPOTTO , IA; KANWAL, R; LATIF, A; REHMAN, NU (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to compare the effectiveness of bupivacaine alone versus bupivacaine combined with lidocaine in patients undergoing ultrasound-guided supraclavicular block. Specifically, the study focused on the onset time and duration of the block effect. The study was designed as a retrospective study in the anesthesia room of the operation theater of Sheikh Zayed Hospital, Lahore, from 2nd November 2021 to 1st May 2022. A total of 200 patients who met the inclusion criteria were included in the study. Prior to the intervention, patients were given midazolam (2mg) to help alleviate anxiety. The participants were then divided into two groups, with 100 patients in each group. Group A received bupivacaine 20 ml (5 mg/ml), while Group B received bupivacaine 10 ml (5 mg/ml) in combination with lidocaine 10 ml (20 mg/ml). The onset and block effect times were recorded in a Performa and subjected to statistical analysis. The results of the study showed that the mean block onset time in Group A (bupivacaine alone) was 9.4±1.34 minutes, while in Group B (bupivacaine plus lidocaine), the mean block onset time was 5.4±0.83 minutes (p=0.000). A comparison of the mean block effect time revealed that in Group A, the mean block effect time was 4±1.34 minutes, while in Group B, the mean block effect time was 6±0.83 minutes. This difference was found to be statistically significant (p=0.000). In conclusion, the study demonstrated that the combination of bupivacaine plus lidocaine was significantly associated with a shorter block onset time and a longer block effect time compared to bupivacaine alone.